Recent Developments and Controversies in the Treatment of Resistant Hypertension - Kühl, C.; Frey, N.; Frank, D. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Resistant hypertension is defined as elevated blood pressure despite the appropriate use of 3 or more antihypertensive drugs, including a diuretic, and constitutes a frequent and important clinical problem with significant disease morbidity and mortality. Several sources of evidence point to the sympathetic nervous system as a major protagonist in this disease entity. The catheter-based, radiofrequency ablation of renal sympathetic nerves (renal denervation) to treat resistant hypertension has sparked great enthusiasm. However, failure of this interventional approach in the randomized, sham-controlled Symplicity HTN-3 trial to reach its efficacy endpoint of attaining a significant blood pressure reduction has called this intervention into substantial question and fueled an ongoing scientific debate. Electrical stimulation of the carotid baroreceptors (baroreflex activation therapy) represents another technique to modulate sympathetic activity currently being studied in several clinical trials. This review summarizes and comments the current literature focusing on the invasive treatment of resistant hypertension.
Keywords: resistant hypertension; treatment adherence; renal denervation; baroreceptor stimulation